Fractionally Cointegrated Vector Autoregression Model: Evaluation of High/Low and Close/Open Spreads for Precious Metals. (November 2018) - Gunay, Samet
Daily high/low and close/open prices are the key parameters of candlestick approach in technical analysis. Besides, the price spreads are also important as they represent an upward or a downward trend. In this study, we investigate the relationship between daily high/low prices and close/open prices for precious metals: gold, copper, palladium, and silver. Empirical analysis has been performed through fractionally cointegrated vector autoregression (FCVAR) model. To observe the relationships, the trends are tested for their characteristics in both states: positive and negative spreads in close/open prices. Results indicated that for a positive trend, high/low spreads have a negative impact on close/open spreads in long run relationship. However, when closing price is less than the opening prices, it is revealed that expanding range in high/low spreads causes a rise in close/open spreads for copper and silver differently from gold price.